2009
DOI: 10.1149/1.3104645
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium Oxide Cathodes for Chlor-Alkali Electrolysis

Abstract: Ruthenium oxide cathodes with low hydrogen overvoltage were manufactured by thermal decomposition method. Catalytic coating was comprised of ruthenium oxide and cerium oxide. Changes of crystalline structure and morphology of catalytic coating by electrolysis were observed. Mechanism of activation and stabilization of ruthenium oxide cathodes was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
3
4
0
Order By: Relevance
“…280.1 eV. This second peak has been attributed to metallic Ru by Näslund et al, which agrees with results from measurements on Ru (0001) performed by Over et al Hachiya et al have also reported formation of metallic Ru in RuO 2 electrodes used for HER at −6 kA/m 2 . In that case, however, the Ru diffraction pattern was only observed after electrolysis for 180 days but not after electrolysis for 30 days (30 times longer than in the work of Näslund et al).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…280.1 eV. This second peak has been attributed to metallic Ru by Näslund et al, which agrees with results from measurements on Ru (0001) performed by Over et al Hachiya et al have also reported formation of metallic Ru in RuO 2 electrodes used for HER at −6 kA/m 2 . In that case, however, the Ru diffraction pattern was only observed after electrolysis for 180 days but not after electrolysis for 30 days (30 times longer than in the work of Näslund et al).…”
Section: Resultssupporting
confidence: 87%
“…In contrast, based on in situ XRD, Chabanier et al concluded that bulk conversion of RuO 2 into metallic Ru does not occur during HER, and Rochefort et al found formation of metallic Ru in the surface unlikely based on XPS measurements. A possible explanation for the differences could be that the electrodes in the studies of Chabanier et al and Rochefort et al were subjected to a lower HER current density and for a significantly shorter time (1 to 2 h) than the electrodes in the studies of Näslund et al and Hachiya et al…”
Section: Resultssupporting
confidence: 74%
“…For strongly alkaline conditions (8−10 M NaOH), this view has been experimentally confirmed. For RuO 2 /Ni cathodes, a hydroxylation process is reported, 194,195 forming first a ruthenium oxyhydroxide phase. Extensive treatment in the HER potential region further transforms the hydrous RuO 2 to metallic Ru.…”
Section: Critical Discussion Of Selected Model Studiesmentioning
confidence: 99%
“…Likewise, microcrystals (Needlelike structure) were observed from 2 to 5 µm wide such as the CeO 2 deposits obtained by electrochemical generation (Figures 5) (Zhou and Switzer, 1996;Zhou et al, 1995). Hachiya et al (2009), synthesized cathodes to obtain sodium hydroxides by the chloralkali process, using a mixture of RuCl 3 and CeCl 3 supported on a Ni mesh, incinerated at 550 °C to obtain RuO 2 and CeO 2 . The cathode electron micrographs show a similar morphology regarding Figure 5d; there were presence of microcrystals, using a cathode in an electrolytic cell, and it was similar to this work.…”
Section: Characterization Of Cerium Oxide Deposit In a Mes Configurationmentioning
confidence: 99%